Rekultywacja biologiczna składowiska odpadów Poznania w Suchym Lesie - Łukasiewicz, Szymon (Wydawnictwo Poznańskiego Towarzystwa Przyjaciół Nauk, 2014)
The Poznań landfill in Suchy Las is a ground level landfill. The subsoil contains heavy clays and silts, which cause it to be naturally isolated from subterranean waters. Outflows from the landfill are directed to the local sewage treatment plant, which functions on the principle of reverse osmosis. The landfill gas is collected by the gas pipeline system and sucked under pressure to the electrical power station. Thanks to these treatments, it is possible and fully justified to plant trees and shrubs as part of the biological reclamation of the landfill. The article discusses the environmental conditions existing at the landfill and the group of arborescent plants that have been successfully planted on the slopes of the landfill.
Keywords: selection of species; tip management; community waste; trees; scrubs; biological reclamation